Visual Basic 2005 in a nutshell - Lomax, Paul (O'Reilly, 2006)
When Microsoft made Visual Basic into an object-oriented programming language, millions of VB developers resisted the change to the .NET platform. Now, after integrating feedback from their customers and creating Visual Basic 2005, Microsoft finally has the right carrot. Visual Basic 2005 offers the power of the .NET platform, yet restores the speed and convenience of Visual Basic. Accordingly, we've revised the classic in a Nutshell guide to the Visual Basic language to cover the Visual Basic 2005 version and all of its new features. Unlike other books on the subject, Visual Basic 2005 in a.